People learn to draw step by step - Powell, William F (Califarnia, USA Walter Foster, 2010)
comparing proportions drwaing facial features rendering figures in action - depicting children
Arts ( Drawing )
1 13
Keywords: Drawing; Figure drawing -- Technique; Human figure in art; Pencil drawing -- Technique